Behaviours of farmed saltwater crocodiles (Crocodylus porosus) housed individually or in groups - Campbell, Dana L. M.; Hewitt, Leisha; Lee, Caroline; Timmerhues, Charlotte A.; Small, Alison H. (Frontiers in Veterinary Science, 2024)
Saltwater crocodiles (Crocodylus porosus) are farmed in Australia primarily for their skins and meat. Commercially, they are raised in group pens as hatchlings and grower crocodiles, then moved to unitised (individual) pens for the final finishing stage when they are several years old. They will exhibit aggressive behaviour toward each other in captivity. Unitised pens can prevent animal injury and teeth marks on the skins but may result in other social restrictions. Research into behavioural housing preferences could assist the industry and inform the process of guideline development for optimal crocodile management and welfare. This study assessed the impacts of two housing systems, unitised or group pens, in 20 commercial finishing crocodiles through measuring behavioural profiles of individuals from video recordings, including housing preference when given a choice. Both pens included water and an above-water shelf, but the crocodiles in unitised pens could also access underneath the shelf. A threat perception test was applied to assess anxiety when housed individually or in groups. However, it was difficult to apply a standardised stimulus to all animals that reliably elicited a behavioral response. Further work would be needed to validate this test for commercial reptiles as the outcomes were not robust. The behavioural observation results showed clear differences in where the crocodiles spent their time across the day and in their activity levels between the pen types. However, interpretation of this variation was confounded by the physical as well as social differences between the pen types given the inconsistency in shelf access. Behaviours exhibited also differed given there were social opportunities in the group pens where individuals were observed engaged in both aggressive and non-aggressive contact interactions. In the free choice environment, crocodiles spent similar amounts of time in both unitised and group pens, suggesting there were features of both pen types that were attractive to the animals. However, skins were damaged from teeth marks highlighting the physical as well as economical risks of group housing. Further work could validate behavioural tests to quantify affective state impacts in different housing environments and whether social interactions do provide benefits for improving crocodile welfare.